Movement Synchrony Over Time: What Is in the Trajectory of Dyadic Interactions in Workplace Coaching? - Erdös, Tünde; Jansen, Paul (Frontiers in Psychology, 2022)
Background: Coaching is increasingly viewed as a dyadic exchange of verbal and nonverbal interactions driving client’s progress. Yet, little is known about how the trajectory of dyadic interactions plays out in workplace coaching. Method: This paper provides a multiple-step exploratory investigation of movement synchrony (MS) of dyads in workplace coaching. We analyzed a publicly available dataset of 173 video-taped dyads. Specifically, we averaged MS per session / dyad to explore the temporal patterns of MS across a) the cluster of dyads that completed 10 sessions, and b) a set of 173 dyadic interactions with a varied number of sessions. Additionally, we link that pattern to several demographic predictors. The results indicate a differential downward trend of MS. Results: Demographic factors do not predict best fitting MS curve types, and only client age and coach experience show a small but significant correlation. Discussion: We provide contextualized interpretations of these findings, propose conceptual considerations and recommendations for future coaching process research and practice.